Dorsal and Ventral Hippocampus Differentiate in Functional Pathways and Differentially Associate with Neurological Disease-Related Genes during Postnatal Development - Lee, A-Ram; Kim, Jong-Hwan; Cho, Eunsil; Kim, Mirang; Park, Mikyoung (Frontiers in Molecular Neuroscience, 2017)
The dorsal and ventral regions of the hippocampus are important in cognitive and emotional processing, respectively. Various approaches have revealed the differential molecular and structural characteristics, and functional roles of the hippocampus. Recent RNA sequencing (RNA-seq) technology has enriched our understanding of the hippocampus by elucidating more detailed information on gene expression patterns. However, no RNA-seqbased study on gene profiles in the developing hippocampus has been reported. Using RNA-seqbased bioinformatic analysis in conjunction with quantitative real-time polymerase chain reaction analysis and a comparison of in situ hybridization data obtained from the Allen Brain Atlas, we provide a thorough analysis of differentially expressed genes in the dorsal and ventral hippocampus at specific developmental ages representing the postnatally maturing hippocampus. Genes associated with particular functional pathways and marker genes for particular neurological diseases were found to be distinctively segregated within either the dorsal or ventral hippocampus at specific or at all developmental ages examined. We also report novel molecular markers enriched in the dorsal or ventral hippocampus. Taken together, this study provides insights into the molecular mechanisms underlying physiological functions linked to the dorsal or ventral hippocampus. The information provided in the study also contributes to a better understanding of brain functions and serves as a resource for future studies on the pathophysiology of dorsal and ventral hippocampal functions.